Adipokine Profiling in Adult Women With Central Obesity and Hypertension - Supriya, Rashmi; Yung, Benjamin Y.; Yu, Angus P.; Lee, Paul H.; Lai, Christopher W.; Cheng, Kenneth K.; Yau, Suk Y.; Chan, Lawrence W. C.; Sheridan, Sinead; Siu, Parco M. (Frontiers in Physiology, 2018)
Central obesity and hypertension are common risk factors for the metabolic syndrome, cardiovascular and renal diseases. Studies have shown that it is more difficult to control blood pressure and prevent end-organ damage in obese individuals with hypertension compared to their non-obese counterparts, especially among women. Obese females have a 6 times higher risk of developing hypertension than non-obese females while obese males are at a 1.5 times higher risk of developing hypertension, compared to their non-obese counterparts. Indeed, the inter-relationship between obesity and hypertension is unclear. Adipokines have been proposed to play a mediating role in the relationship between obesity and hypertension and are involved in the pathogenesis of metabolic diseases. Therefore, this study sought to determine the role of adipokines (adiponectin, plasminogen activator inhibitor-1, leptin, and tumour necrosis factor-α) in hypertensive Hong Kong Chinese women with central obesity. A total of 387 women aged 58 ± 11 years who were examined with a 2 x 2 factorial design for central obesity (waist circumference ≥ 80 cm) and hypertension (blood pressure ≥ 140/90 mmHg), were recruited from a pool of 1,492 Hong Kong Chinese adults who were previously screened for metabolic syndrome. Subjects with hyperglycemia, hypertriglyceridemia, and dyslipidemia were excluded to eliminate confounding effects. Our findings revealed that hypertensive women with central obesity had a lower anti-inflammatory status (adiponectin) and a higher pro-inflammatory status (TNF-α) than obese alone or hypertensive alone women. Also, women with central obesity had higher circulatory PAI-1 and leptin concentrations than their non-obese counterparts. We conclude that obesity may shift towards a more pro-inflammatory state and may become more severe in the presence of hypertension or vice versa.